(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The current situation with sheepbreeding in the Kyrgyz Republic requires a creation of new system of work with manufacturers of raw stuff from sheep and establishment of marketing ways for obtaining extra funds. A structure of enterprises and interchange of procedures for raising profitability of merino sheep breeding.